College Students’ Perception of Using Tiktok to Learn Vocabulary - Vera Nurlia (Jurnal Pustaka Cendekia Pendidikan, 2023)
Technology has significantly changed how learning and teaching are done in recent years. TikTok is one of the technological tools that many younger generations use today. The most crucial aspect of a language is vocabulary; using this appealing tool, learners can expand their vocabulary. By watching videos and following accounts that can provide English vocabulary lessons, TikTok social media users can also learn new words and phrases more interestingly and interactively. This study uses a quantitative method to study the perceptions of Informatics Engineering students at Cendekia Abditama University in using social media TikTok to increase English vocabulary and how TikTok video content can contribute to students' vocabulary learning goals so that their English vocabulary can increase. Data for the study are gathered quantitatively through a survey questionnaire. There are 50 Informatics Engineering students involved. The results show that students have a favorable perception toward utilizing TikTok to learn English vocabulary. Students also point out that TikTok provides a variety of tools and settings that help to increase English vocabulary.